Associations of exposure to cadmium, antimony, lead and their mixture with gestational thyroid homeostasis. (15th November 2021) - Margetaki, Katerina; Vafeiadi, Marina; Kampouri, Mariza; Roumeliotaki, Theano; Karakosta, Polyxeni; Daraki, Vasiliki; Kogevinas, Manolis; Hu, Howard; Kippler, Maria; Chatzi, Leda
Abstract: Maintaining thyroid homeostasis during pregnancy is vital for fetal development. The few studies that have investigated associations between metal exposure and gestational thyroid function have yielded mixed findings. To evaluate the association of exposure to a mixture of toxic metals with thyroid parameters in 824 pregnant women from the Rhea birth cohort in Crete, Greece. Concentrations of three toxic metals [cadmium (Cd), antimony (Sb), lead (Pb)] and iodine were measured in urine using inductively coupled plasma mass spectrometry and thyroid hormones [Thyroid Stimulating Hormone (TSH), free thyroxine (fT4), and free triiodothyronine (fT3)] were measured in serum in early pregnancy. Associations of individual metals with thyroid parameters were assessed using adjusted regression models, while associations of the metal mixture with thyroid parameters were assessed using Bayesian Kernel Machine Regression (BKMR).Women with high (3rd tertile) concentrations of urinary Cd, Sb and Pb, respectively, had 13.3 % (95%CI: 2.0 %, 23.2 %), 12.5 % (95%CI: 1.8 %, 22.0 %) and 16.0 % (95%CI: 5.7 %, 25.2 %) lower TSH compared to women with low concentrations (2nd and 1st tertile). In addition, women with high urinary Cd had 2.2 % (95%CI: 0.0 %, 4.4 %) higher fT4 and 4.0 % (95%CI: −0.1 %, 8.1 %) higher fT3 levels, and women with high urinary Pb had 4 % (95%CI: 0.2 %, 8.0 %) higher fT3 levels compared to women with low exposure. The negative association of Cd with TSH persisted only when iodine sufficiency was unfavorable. BKMR attested that simultaneous exposure to toxic metals was associated with decreased TSH and increased fT3 and revealed a potential synergistic interaction of Cd and Pb in association with TSH. The present results suggest that exposure to toxic metals even at low levels can alter gestational thyroid homeostasis. Graphical abstract: Image 1 Highlights: Cadmium was associated with decreased TSH and increased fT3 and fT4. Antimony was associated with decreased TSH. Lead was associated with decreased TSH and increased fT3. The mixture of the metals was associated with decreased TSH and increased fT3. Iodine modified the observed associations.